A probabilistic approach for estimating the seismic response of elasto-plastic SDOF systems. - Ambrisi, Angelo D. (Earthquake engineering & structural dynamics.)
The seismic response of elasto-plastic structures to both recorded and generated accelerograms is characterized by a large scattering of the results, even for accelerograms with similar peak ground acceleration values and frequency content. According to current code recommendations a design value of the seismic response of an elasto-plastic structure can be computed as the mean of the responses to a certain number of spectrum fitting generated accelerograms. A more effective probabilistic approach is presented herein. It allows the analyst to calculate a design value of the seismic response characterized by a predefined non-exceedance probability using a limited number of generated accelerograms. The results of the performed analyses are presented in diagrams that can be used for structural design applications. The applicability of the proposed method is demonstrated in the case of an elasto-plastic structural system and the results are compared with those obtained applying current code recommendations.